The Correlation between Language Learning Strategy and Student Motivaton in Writing Achievement - Sholehati, Yetik; Ribut Sabar Tono; Ika Desy Wardhani (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2025)
The study aims to investigate the relationship between language learning strategies and student motivation in writing achievement. This study employed quantitative methods. The participants in the study were 14 seventh-grade students from a junior high school in Jember. In this study, the researcher utilized both a questionnaire and an interview, selecting a sample for the purpose. Two types of tools were employed: a questionnaire assessing language learning strategies and student motivation. The results indicated that the average score for the questionnaire was language acquisition 852 points. Subsequently, the average motivation score for students was 858. The data indicated that it was similarly classified as having a good correlation. From the data, the researcher obtained the correlation index: rxy was 1.710, indicating a strong correlation. This indicates a positive relationship between language learning strategies and student motivation in writing achievement